IDENTIFIKASI GUGUS FUNGSI DAN KANDUNGAN MINERAL LEMPUNG PACITAN DENGAN SPEKTROSKOPI INFRA RED (IR) X-RAY DIFFRACTION (XRD) - Soleman, Pangoloan (Sistem Informasi, 2011)
Clay is natural mineral from silicate family like crystal which has approximately 2 micrometer. There are two component unit of atom in clay mineral. One consists of oxygen or hidroksida with alumunium, iron or magnesium that coordinated in octahedral system. Others, it is tetrahedral system from silicon with oxygen or hidroksida. Based on IR analysis, it can be known that metalâOH bending vibrations it can be seen at 912,3 cmâ1 wavelength. On the other bands between 694,3 and 754,1 cmâ1 that are SiâO bending vibrations. X-Ray Diffraction (X-RD) analysis be seen main peak at 2ï± = 5,70o (d001=15,48 Ã) and 2ï± = 20,02o (d001=4,43 Ã). That are for smectite mineral kind montmorillonite as main unit in clay from Pacitan